2004
DOI: 10.1104/pp.104.043323
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Different Gene Enrichment Approaches Toward Identifying and Sequencing the Maize Gene Space

Abstract: Maize (Zea mays) possesses a large, highly repetitive genome, and subsequently a number of reduced-representation sequencing approaches have been used to try and enrich for gene space while eluding difficulties associated with repetitive DNA. This article documents the ability of publicly available maize expressed sequence tag and Genome Survey Sequences (GSSs; many of which were isolated through the use of reduced representation techniques) to recognize and provide coverage of 78 maize full-length cDNAs (FLCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…About 91.5% of all genes were detected by at least one GSS tag. A previous comparison of CF and MF with a set of 78 full-length cDNAs also showed that 95% of the cDNAs are tagged by at least one sequence read (Springer et al 2004). However, total nucleotide coverage of the full-length cDNAs approached 75%, although this obviously included only exons.…”
Section: Dna Methylation Of the Maize Regionsmentioning
confidence: 99%
“…About 91.5% of all genes were detected by at least one GSS tag. A previous comparison of CF and MF with a set of 78 full-length cDNAs also showed that 95% of the cDNAs are tagged by at least one sequence read (Springer et al 2004). However, total nucleotide coverage of the full-length cDNAs approached 75%, although this obviously included only exons.…”
Section: Dna Methylation Of the Maize Regionsmentioning
confidence: 99%
“…For example, the localization of markers flanking the BAC contigs by FISH will be an effective strategy to estimate the gaps between contigs. The Assembled Zea mays (AZM) sequences are the assembly of methylation filtered and high Cot sequence reads representing 95% of genic sequences in the maize genome, and many of them have been anchored to genetic map and BAC contigs (Springer et al, 2004). Thus, AZM sequences can be used as FISH probes for representing BAC clones or single-copy genes.…”
Section: Applications Of Hr Gene Fishmentioning
confidence: 99%
“…Gene contigs can be ordered by using end sequences of methylation-spanning linker library clones, which consist of blocks of repetitive DNA flanked on either side by genic regions (8), by superimposing the contigs on a lowredundancy sequence of the entire genome or anchoring them to a genetic map. It is estimated that the gene discovery ability of these combined technologies is significantly Ͼ95% (9). Alternative strategies are based on the fact that genes are not evenly distributed over a genome (10)(11)(12)(13).…”
mentioning
confidence: 99%